2022
DOI: 10.3390/designs6050090
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Triangular Modular Structures for Roadside Service Buildings

Abstract: The need for a relatively quick solution to the problem of providing highways with roadside service facilities necessitates the development of a series of appropriate standard projects. To increase the efficiency of these series, it is advisable to carry out the interconnection of space-planning solutions based on a particular module. Taking into account the variety of planning and landscape characteristics of the sites for the placement of objects of the mainline service, it seems advisable to choose as a mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…According to the necessity for the development of appropriate standard projects for providing highways with roadside service facilities and increasing efficiency, Samoilov et al [7] suggested interconnecting space-planning solutions based on a triangular module instead of a square or rectangular one. According to the results of this research, the use of this modular system can help reduce the harmful impact on the environment and effectively utilize renewable energy sources [7].…”
mentioning
confidence: 99%
“…According to the necessity for the development of appropriate standard projects for providing highways with roadside service facilities and increasing efficiency, Samoilov et al [7] suggested interconnecting space-planning solutions based on a triangular module instead of a square or rectangular one. According to the results of this research, the use of this modular system can help reduce the harmful impact on the environment and effectively utilize renewable energy sources [7].…”
mentioning
confidence: 99%